PERILAKU CREEP PADA KOMPOSIT POLYESTER YUKALAC 157 BQTN-EX DENGAN FILLER SERAT GELAS - Dodi Marlin; . Sugiyanto; . Zulhanif (Jurnal Ilmiah Teknik Mesin, 2013)
Research aims to investigate the creep behavior of the composite which made from polyester resin with fiberglass filler. Composites are composed from fiber glass with pararel oriented, then the composition of the fiber volume to matrix are vary at 5%: 95%, 10%: 90%, and 15%: 85%.Composite then casted based on dimensions listed in ASTM D2990. Composites tested with the tensile test to determine the tensile strength of the composite. The test is continue with creep testing by providing creep load on the testing 60% of the tensile strength. In order to know the mechanism of failure in the plane of composite fracture, SEM is used to observing it. The test result showed that the composite with the volume composition of the fiber versus matrix : 15 %: 85%, has the longest time of all variations although just only 1000 seconds.The low creep time due to presence of voids in the composite matrix, fiber breaking, pull out, debonding at the fiber and also the influence of loading during creep testing are not uniform.With a maximum creep only 1000 seconds, the composite results of this study are not feasible to be applied in both the shipping industry andautomotive.Keywords: polymer composite, Polyester, Fiber glass, creep behaviour